READINESS OF TRANSIT ORIENTED DEVELOPMENT (TOD) CONCEPT IMPLEMENTATION IN PERAK’S SUBURBAN AREAS - Ahmad, Sabri; Rashid, Mohamad Fadhli; Suratman, Robiah (PLANNING MALAYSIA, 2022)
The transit-oriented development (TOD) concept is a planning strategy in metropolitan areas that involves mixed use of land for transportation systems, especially railway stations, as the basis for planning the TOD concept. The question raised is whether suburban areas are suitable and ready to implement the TOD concept which is included in the suburban districts’ local plan. The aim of this paper is to evaluate the readiness of implementing the TOD concept model for 14 suburban railway station areas in seven of Perak’s local government administrations. The methodology used is a mixed quantitative and qualitative approach, applying the Fuzzy Delphi Method (FDM) and case study method to develop the readiness model and evaluate the readiness level of the TOD concept in suburban areas. Twenty indicators from 4 key elements in the TOD readiness model were identified, such as population density, transit system, economic development, and land development potential. The findings indicated that all 14 railway stations involved have not yet achieved a 100 per cent level of readiness in implementing the TOD concept model.